Overweight and Its Associated Factors among Women of Reproductive Age in Dire Dawa, Eastern Ethiopia, 2021: Community-Based Cross-Sectional Study - Ismael Omer; Tariku Derese; Yitagesu Sintayehu (Hindawi Limited, 2022)
Background. Overweight in women of reproductive age is a major public health concern in developing countries because of overconsumption of low-quality food. Currently, being overweight is a major health concern worldwide. It exposes humans to various health problems. In Ethiopia, despite the trend indicated increasing in overweight, priority is given for undernutrition. In Dire Dawa, there is scarce evidence regarding reproductive age overweight. Therefore, this study is designed to assess the prevalence of overweight and its associated factors among women of reproductive age in eastern Ethiopia. Methods. A community-based cross-sectional study was conducted from May 15 to June 15, 2021, in Dire Dawa, Eastern Ethiopia; a multi-stage systematic sampling technique was used to select 559 women aged 15-49 years. Data were collected through face-to-face interviews using a structured pretested questionnaire. Ninety-five percent CI was used to identify the factors associated with overweight while controlling for all possible confounders using multivariable logistic regression. Statistical significance was set at a P-value of 0.05. Results. The results of this study revealed that the prevalence of overweight was 63.1% (95% CI: 59.0, 67.2). Overweight was significantly associated with weekly discretionary calories (AOR = 3.964, 95% CI (1.131, 13.894)), contraceptive use (AOR = 2.838, 95% CI (1.443, 5.580)), and monthly family income (AOR = 3.916, 95% CI (1.352, 11.340)). Conclusion. Overweight among women of reproductive age was high in Dire Dawa city. Discretionary calories per week, family monthly income, and contraceptive use were significantly associated with overweight. Developing and implementing community-based culturally sensitive, feasible, and potentially high-impact intervention to address the modifiable risk factors among women of reproductive age is critical.